Fungal diseases of cotton plant Gossypium hirsutum L. in Bangladesh (Dhaka University Journal of Biological Sciences, 2011)
Seven types of symptom were recorded in four varieties such as CB3, CB9, Hill cotton 1 (HC-1) and 2 (HC-2) of cotton (Gossypium hirsutum L.) during July, 2005 to June, 2008. The symptoms were Anthracnose, Alternnaria leaf spot, Boll rot, Cercospora leaf spot, Rust, Sclerotium rot and Wilting. Present study revealed that association of 30 species of fungi which belonged to 21 genera such as one one in Zygomycetes, one in Ascomycetes, one in Basidiomycetes, 18 in Deutermycetes and one in sterile fungus. The isolated fungi were Alternaria alternata (Fr.) Keissler, Arthrinium sp., Ascochyta sp., Aspergillus flavus, Link., Aspergillus niger Van Tiegh, Aspergillus sp., Botryodiplodia sp., Cercospora sp., Chaetomium sp., Chaetophoma sp., Cladosporium sp., Colletotrichun coffeanum Noack, z. f. Pflan zenko., Colletotrichum spp., Curvularia clavate Jain, Curvularia lunata (Wakker) Boedijn, Fusarium moniliforme, Wr. and Reink, Fusarium spp., Nigrospora sp., Pestalotia sp., Penicillium sp., Phoma sp., Pteroconium sp., Puccinia sp., Rhizopus stolonifer (Ehrenb. Ex. Fr) Lind, Sclerotium rolfsii Sacc., Trichoderma viride Pers. ex Fries. and one sterile fungus. Fusarium spp. and Colletotrichum spp. were frequently associated with all the four cotton varieties examined. Botryodiplodia sp. was associated with Hill Cotton 1 (HC-1) and Hill Cotton 2 (HC-2). Sclerotium rolfsii was found associated with CB-3 cotton variety. Key words: Fungal diseases; Cotton plant; Gossypium hirsutum; Bangladesh DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8974 DUJBS 2011; 20(2): 139-146